The Effect of Dietary Aflatoxin on Local Domestic Turkey (Meleagris gallopavo) in Libya (Al-Farooq Journal of Sciences, 2026)
This study was conducted to determine the effects of feed contaminated with aflatoxin B1 (AFB1) on growth performance in Turkey. Sixty, ducks randomly divided into two groups of 3 replicates and were fed commercial feed uncontaminated or contaminated AFB1 at level 250 µg/kg. AFB1 contaminated feed significantly decreased the body weight, feed intake and increased feed conversion rate (p
Keywords: Probiotic, Aflatoxin, Digestibility, Performance, Domestic Turkey, Libya